2021
DOI: 10.3390/educsci11110728
|View full text |Cite
|
Sign up to set email alerts
|

Digital University Teaching and Learning in Management—The Gini from the COVID-19 Bottle and Its Empirical Representations in Germany

Abstract: Digitalization of teaching, learning, and assessment in higher education has gained increasing attention in research in the recent years. While previous research investigated issues of effectiveness, course attendance, and course evaluation from a long-term perspective, the current COVID-19 pandemic forced higher education institutions to digitalize teaching, learning, and assessment in a very short time. In this context, we investigate the effects of the digitalization of three courses from operations researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…Accordingly, it was revealed that students' attitudes towards academic procrastination decrease when the level of perceived digital competences increases. Consistently, prior research supports this result in the context of higher education (Kaliba & Ambrožová, 2021;Rahardjo et al, 2013;Sage et al, 2021;Witt et al, 2021). Apparently, this finding proves that digital competences have a significant effect on academic procrastination in the post-pandemic period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Accordingly, it was revealed that students' attitudes towards academic procrastination decrease when the level of perceived digital competences increases. Consistently, prior research supports this result in the context of higher education (Kaliba & Ambrožová, 2021;Rahardjo et al, 2013;Sage et al, 2021;Witt et al, 2021). Apparently, this finding proves that digital competences have a significant effect on academic procrastination in the post-pandemic period.…”
Section: Discussionsupporting
confidence: 86%
“…In the post-pandemic period, as a result of digitallysurrounded learning environments in HEIs, it is significant to reconsider the impact of digital competences on academic procrastination; however, the current research on these two variables investigated among students is quite scarce (Kaliba & Ambrožová, 2021;Rahardjo et al, 2013;Sage et al, 2021;Witt et al, 2021). Kaliba and Ambrožová (2021), in their study with 322 university students in the Czech Republic, reported that the student tendencies to procrastinate during online learning were stronger than the regular learning, and underlined the impact of digital competences of the teacher and the application of the digital tools on procrastination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation